(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This paper presents specific nature of project management of EU-fundedproject. It alsoshownhow themanagement accounting supportsthe management in this type of project. Because of limitedcontent ofthe article there are presented only two instruments of management accounting that can be use in Eu-funded project: budgeting and EVM.